An insect boring in an Early Cretaceous wood from Bornholm, Denmark. Issue 3 (2nd July 2020) - Mikuláš, Radek; Milàn, Jesper; Genise, Jorge F.; Bertling, Markus; Bromley, Richard G.
Abstract: An insect boring of unique shape is described from a lignitic layer within the Early Cretaceous (Berriasian) Skyttegård Member of the Rabekke Formation on Bornholm. Morphologically it cannot be compared to any modern or fossil wood borings, although some structures are reminiscent of Scolytidae, Platypodidae and Lymexylonidae. Most probably, however, the tracemaker was a female fungus-farming beetle, thus producing an agrichnion.